Effects of Aroclor 1254 and vitamin E on bone oxidant/antioxidant status in adult, pregnant rats and their pups - Dogan, A.; Erisir, M. (Ecole Nationale Veterinaire Toulouse, 2012)
The aim of the study was to analyze the oxidant and antioxidant parameters in bone tissue of offspring from pregnant rats, pregnant rats and not pregnant female rats exposed to Aroclor 1254 alone or associated to the vitamin E. A total of 30 pregnant Sprague-Dawley rats and 30 adult rats were divided into 3 equal groups according to the treatments instituted during the pregnancy period (20 days) with subcutaneous daily injections of Aroclor 1254 (2 mg/kg/day) alone or associated with vitamin E (50 mg/kg/day) or normal saline in controls. The oxidant/antioxidant balance in bone was investigated by determining the malondialdehyde (MDA) and glutathione (GSH) contents as well as the superoxide dismutase (SOD), catalase (CAT), the glutathione peroxidase (GSH-Px) and glutathione reductase (GR) activities in females and in their progeny (10 pups per groups). Treatment with Aroclor alone has induced significant decline in GSH content in pregnant females compared to the not treated ones and significant increases in GR and GSH-Px activities in pups whereas GSH content and the CAT activity were significantly depressed in pregnant females cotreated with Aroclor and vitamin E compared to the pregnant controls and GSH content, the GR and CAT activities were markedly enhanced in pups. Although alterations were noticed in the antioxidant systems, no significant variations in MDA contents were evidenced, suggesting that the period of pregnancy for Aroclor and/or Vitamin E treatments was too short for inducing ROS accumulation in rats.
Keywords: Rat; polychlorinated biphenyls; Aroclor 1254; vitamin E; pregnancy; progeny; oxidative stress; antioxidants; bone